Financial Freedom for Millennials: Smart Strategies in the Age of Innovation - Muslim, Ahmad Bukhori; Sulistyorini Wulandari, Dian; Zulfikar, Elfateh (Journal of International Multidisciplinary Research, 2024)
This study explores the influence of financial literacy, financial inclusion, and lifestyle on financial management among millennials, with a case study of students from the Faculty of Economics and Business at Universitas Pelita Bangsa. Using a quantitative approach and purposive sampling technique, data were collected from 100 respondents through a questionnaire and analyzed using multiple linear regression. The results show that financial literacy, financial inclusion, and lifestyle positively and significantly impact student financial management, with significance values of 0.000 and 0.007 (< 0.05). These findings highlight the importance of these three factors in managing finances in the millennial era.